2003
DOI: 10.1007/s00134-003-1699-x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae strain-dependent lung inflammatory responses in a murine model of pneumococcal pneumonia

Abstract: These findings confirm that the production of the pro- and anti-inflammatory mediators are critically dependent not only upon the different species of bacteria used to establish the experimental infection but also upon the different strains of a specific bacterial species used, i.e., S. pneumoniae in this study. These substantially different host responses were not serotype dependent. Moreover, the profile of lung pro-and anti-inflammatory cytokines within 48 h postinfection, at least in this pneumonia model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 43 publications
2
15
0
2
Order By: Relevance
“…The tissue inflammatory response to pneumococcal pneumonia is a function of the mouse (58) and the pneumococcal strain (52). In our study, the predominantly interstitial inflam- D).…”
Section: Discussionmentioning
confidence: 68%
“…The tissue inflammatory response to pneumococcal pneumonia is a function of the mouse (58) and the pneumococcal strain (52). In our study, the predominantly interstitial inflam- D).…”
Section: Discussionmentioning
confidence: 68%
“…Over 90 serotypes of S. pneumoniae have been characterized to date, all with differing levels of pathogenicity and virulence factor expression, resulting in differential prevalence in the human population [20][21][22][23] . Similarly, in mice, it has been reported that the extent of, and kinetics associated with, the immune response elicited in response to a nasopharyngeal colonization is dependent on the colonizing strain itself 24 . Thus, selection of an appropriate strain to utilize for the establishment of a nasopharyngeal colonization is not a trivial matter, nor is selection of mouse genetic background.…”
Section: Discussionmentioning
confidence: 95%
“…The oropharynges were transilluminated, and the tracheas were cannulated with needles attached to microliter syringes containing the pneumococcal suspension (12). This model is still used in several studies on drug efficacy, host response to infection, and the role of pneumococcal virulence factors in the disease (1,11,19,168,169,208,237). Another i.t.…”
Section: Mouse Modelsmentioning
confidence: 99%